DETERMINING CRITICAL SUCCESS FACTORS OF MOBILE BANKING ADOPTION IN IRAQ - Nawar Makttoof (Scholar Express Journals, 2023)
The purpose behind using Mobile banking (M-banking) may bedescribed as one of the services offered by a bank or other financialorganization that enables its clients to do a range of banking activities using amobile device, like a tablet, personal digital assistant or smart phone .
Keywords: Mobile banking; m-banking; extended TAM; mobile banking adoption; consumers